Representações surdas na desconstrução de práticas ouvintistas : um estudo crítico e emancipatório - Gontijo, Túlio Adriano Alves (2020)
Law 10.436 / 2002 recognizes Libras - Brazilian Sign Language - as the official language of the deaf community, based on this legal framework, the deaf community intensifies its struggle for cultural recognition, respect for their identities and for the effective use and diffusion of Libras. Both the current legislation and the creation of the Letras Libras course, in 2006, contributed significantly to the knowledge, teaching and diffusion of Libras throughout the national territory. The study has as theoretical scope the precepts of Systemic Functional Linguistics (Halliday, 1994); Critical Realism (BHASKAR, 1978; 1989); Critical Discourse Analysis (FAIRCLOUGH, 1989; 2003) e; Ouvistismo (WRIGLEY, 1996; SKLIAR 2012; 2016; LAGES, 2019). This research aims to investigate the linguistic-discursive representations of the deaf community of a Higher Education Institution, focused on the issue of linguistic and cultural empowerment of the Deaf, in the search for self-empowerment of the hearing influence. To this end, a qualitative research of an emancipatory nature was carried out, following 4 stages: (a) analysis of the situation through annotations, in order to understand how the empowerment of the deaf in the institution happens, for the construction of the guiding themes; (b) filmed meeting of the focus group with discussions on the topics of hearing(nism), linguistic prejudice, colonialism, among others; (c) translation and transcription of statements; (d) carrying out the analyzes, first of linguistic materiality, based on the theoretical-methodological subsidies of the SFL and, later, discursive analysis in the light of the RC and the ACD. The results show that the course has many positive points, but that even though Letras Libras is a bilingual and bicultural course, it still perpetuates some hearing practices, considered reflections of the Milan Congress of 1880. Therefore, there is a need for changes in the course structures so that these practices are dissipated so that deaf students have the same learning conditions as those of hearing students. It is hoped, with this research, to contribute to changes in social practices regarding the depravity of the Deaf mediated by the mechanisms of human emancipation.